Congenital intrahepatic portosystemic shunt in 27 children: an experience and treatment strategy of a single centre in China - Zhang, Jin-Shan (Frontiers in Pediatrics, 2024)
Objective: To evaluate treatment strategies for congenital intrahepatic portosystemic shunt (CIPSS) based on the experience of treating 27 children.Between August 2017 and January 2024, our team treated 27 children with CIPSS.Twelve patients underwent surgical ligation of the portosystemic shunt, while 15 patients diagnosed prenatally received conservative treatment without surgery. All patients were followed up after diagnosis or surgery. During follow-up, blood ammonia and biochemistry tests, along with ultrasound examinations, were conducted. Clinical presentations were recorded.The prenatal diagnosis rate for CIPSS using ultrasound was 74.1% (20/27).Hyperammonemia was the most common clinical manifestation, occurring in 81.5% (22/27) of cases. Jaundice and abnormal liver function were the next most frequent presentations in patients with prenatal diagnosis, with incidences of 80% (16/20) and 65% (13/20), respectively. In 12 patients undergoing surgical ligation, blood ammonia levels returned to normal, the abnormal shunt disappeared as confirmed by ultrasound and CT, and no patients developed portal vein thrombosis or portal hypertension postoperatively. In 15 patients receiving conservative treatment, 53.3% (8/15) experienced spontaneous closure of the abnormal shunt within 1 to 7 months (median: 3 months). Jaundice and hyperammonemia were completely resolved within 1 to 8 months in patients receiving conservative treatment.CIPSS is a curable congenital anomaly. Prenatal ultrasound is effective for detection.Conservative treatment is recommended until the age of one, followed by surgical ligation or interventional treatment for patients with persistent shunts after one year.